Analisis Sentimen Aplikasi Quara Menggunakan Algoritma Naive Bayes - Ambarita, Natasya Yonike (JUSS (Jurnal Sains dan Sistem Informasi), 2021)
This project seeks to utilize the Naive Bayes algorithm to analyze the sentiment in user evaluations of the Quora app on the Google Play Store. This research offers further depth into users' perceptions of Quora using review sentiment analysis, which aids developers in enhancing the user experience. Data from user reviews on the Google Play Store are gathered for this study using the web scraping technique. Data collection, preprocessing, labeling, TF-IDF weighting, data split into training and test data, classification using the Nave Bayes method, and model assessment were the steps of the research. The findings demonstrate that the Naive Bayes algorithm is 88% accurate in classifying the sentiments of user reviews. It is advised to conduct further study to expand data volume, employ feature selection, and boost accuracy.